The Clinical Importance of the Mercury Problem in Artisanal Small-Scale Gold Mining - Afrifa, Justice; Opoku, Yeboah Kwaku; Gyamerah, Eric Ofori; Ashiagbor, George; Sorkpor, Rosemary Doe (Frontiers in Public Health, 2019)
Artisanal small-scale mining is widely operated in various countries serving as a livelihood to many rural communities. However, it is a significant source of environmental mercury contamination which affects human health. Amalgamation and amalgam smelting, two significant steps in the artisanal small-scale mining operations generate loads of mercury vapors leading to chronic exposure among miners. Thus, this article seeks to provide a topical review of recent findings on organ damage and metabolic disorders among mercury-exposed artisanal small-scale miners with emphasis on the contributing factors such as personal protective equipment usage and artisanal small-scale gold mining-specific occupational activities. Also, insights into the effect of mercury intoxication and mechanisms of action on organ and metabolic systems among exposed individuals are also provided.